Hubungan Letak Lesi dengan Derajat Spastisitas pada Pasien Stroke Iskemik di RSUD Ulin Banjarmasin - Andi Ari Sandy; Fakhrurrazy Fakhrurrazy; Didik Dwi Sanyoto (Homeostasis, 2020)
Abstract: Ischemic stroke occurs due to decreased blood flow due to emboli or thrombosis that is temporary or permanent in the cerebral arteries. Stroke has several symptoms such as facial paralysis, limbs or spasticity and can cause death. Spasticity is affected by the location of the lesion. The purpose of this study was to analyze the relationship between the location of the lesion with the degree of spasticity in ischemic stroke patients at Banjarmasin District Hospital based on the Modified Ashworth Scale (MAS). This research is an observational analytic and cross-sectional approach. The MAS examination is carried out after the respondent fulfills the inclusion and exclusion criteria. A total of 30 samples obtained by purposive sampling obtained 6 cortical lesions in the patient, 16 subcortical lesions in the patient, and 8 in the basal ganglia lesion in 8 patients. The degree of MAS in patients was found with the normal category of 6 patients, the moderate category of 19 patients, and the weight category of 5 patients. Analysis using the Kormogorov-Smirnoff correlation test showed an insignificant value of p = 0.841. The conclusion that there is no relationship between the location of the lesion with the degree of spasticity in ischemic stroke patients at Ulin Hospital Banjarmasin. Keywords: Ischemic stroke, location of the lesion, spasticity, Modified Ashworth Scale. Abstrak: Stroke iskemik terjadi akibat penurunan aliran darah karena emboli atau trombosis yang bersifat sementara atau permanen di arteri serebral. Stroke memiliki beberapa gejala seperti kelumpuhan wajah, anggota badan atau spastisitas dan dapat menyebabkan kematian. Spastisitas dipengaruhi oleh letak lesi. Tujuan penelitian ini untuk menganalisis hubungan antara letak lesi dengan derajat spastisitas pada pasien stroke iskemik di RSUD Banjarmasin berdasarkan Modified Ashworth Scale (MAS). Penelitian ini bersifat observational analitik dan pendekatan cross-sectional. Pemeriksaan MAS dilakukan setelah responden yang memenuhi kriteria inklusi dan eksklusi. Sebanyak 30 sampel didapatkan secara purposive-sampling didapatkan lesi pada kortikal sebanyak 6 pasien, lesi pada subkortikal sebanyak 16 pasien, dan lesi pada ganglia basalis sebanyak 8 pasien. Derajat MAS pada pasien ditemukan dengan kategori normal 6 pasien, kategori sedang 19 pasien, dan kategori berat 5 pasien. Analisis menggunakan uji korelasi Kormogorov-Smirnoff  menunjukkan nilai tidak signifikan p=0,841. Kesimpulan bahwa tidak terdapat hubungan letak lesi dengan derajat spastisitas pada pasien stroke iskemik di RSUD Ulin Banjarmasin. Kata-kata kunci: Stroke iskemik, letak lesi, spastisitas, Modified Ashworth Scale.